The Effect of Contextual Teaching and Learning (CTL) Based on Lesson Study on the Biology Learning Achievement of High School Students - Uswatun Hasanah; Suratno Suratno; Mochammad Iqbal (Pancaran Pendidikan, 2019)
The implementation of Contextual Teaching and Learning (CTL) based on lesson study aimed to determine its effect on the biology learning achievement of high school students. This referred to quasi-experimental research by applying CTL learning based on lesson study to the experimental class and conventional learning in the control class. The population in this study amounted to 286 students (Science X class students of SMA Negeri 2 Jember). The sample in this study was determined through homogeneity test, normality test, and random sampling to determine the control class and the experimental class. The students' affective learning achievement was analyzed by using the independent sample t-test, while their cognitive learning achievement was analyzed by using ANAKOVA test. Based on the test results of the independent sample t-test, it was found that the students' affective learning achievement differed significantly between the students in experimental class and control class. Based on the results of ANAKOVA test, it was known that the application of CTL learning based on Lesson Study has a significant effect on students' cognitive learning achievement.